2016
DOI: 10.1590/1516-3180.2015.01382111
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vitamin B12 deficiency in type 2 diabetic patients using metformin: a cross-sectional study

Abstract: CONTEXT AND OBJECTIVE: The prevalence of vitamin B12 deficiency varies from 5.8% to 30% among patients undergoing long-term treatment with metformin. Because of the paucity of data on Brazilian patients, this study aimed to determine the frequency of B12 deficiency and related factors among Brazilian patients with type 2 diabetes mellitus (T2DM) using metformin. DESIGN AND SETTING: Cross-sectional study at a public university hospital. METHODS:Patients with T2DM and a control group of non-diabetics were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 39 publications
1
51
2
4
Order By: Relevance
“…Another study by Sparre Hermann et al reported a 26.7% prevalence of vitamin B 12 deficiency in metformin-treated T2DM patients in Sweden [29]. Additionally, a study by Damião et al [30] and Pflipsen et al [23] found a 22.5% and 22% prevalence of B 12 deficiency among Brazilian and American T2DM patients using metformin. Wulffele [10,12,27,31].…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Sparre Hermann et al reported a 26.7% prevalence of vitamin B 12 deficiency in metformin-treated T2DM patients in Sweden [29]. Additionally, a study by Damião et al [30] and Pflipsen et al [23] found a 22.5% and 22% prevalence of B 12 deficiency among Brazilian and American T2DM patients using metformin. Wulffele [10,12,27,31].…”
Section: Discussionmentioning
confidence: 99%
“…29 Damião CP et al, conducted a cross sectional clinical trial with 462 T2DM patients on metformin in Brazil. 30 The study demonstrated vitamin B12 deficiency in 22.5% of patients on metformin as compared to 7.4% of controls. The mean serum vitamin B12 was 272 pg/ml and was significantly (p <0.001) lower than controls with 348 pg/ml.…”
Section: Discussionmentioning
confidence: 85%
“…Similar studies done in Europe have reported a prevalence of about 27%. 16,17 Akabwai et al 18 , Study has shown that the prevalence of vitamin B12 deficiency was 10. 7%.…”
Section: Disscussionmentioning
confidence: 99%